2011
DOI: 10.1056/nejmoa1011418
|View full text |Cite
|
Sign up to set email alerts
|

Iniparib plus Chemotherapy in Metastatic Triple-Negative Breast Cancer

Abstract: The addition of iniparib to chemotherapy improved the clinical benefit and survival of patients with metastatic triple-negative breast cancer without significantly increased toxic effects. On the basis of these results, a phase 3 trial adequately powered to evaluate overall survival and progression-free survival is being conducted. (Funded by BiPar Sciences [now owned by Sanofi-Aventis]; ClinicalTrials.gov number, NCT00540358.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
469
1
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 748 publications
(483 citation statements)
references
References 27 publications
5
469
1
8
Order By: Relevance
“…259 Although PARP inhibitors administered as monotherapy was found ineffective in triple-negative breast cancer, experimental evidence has indicated synergistic lethality between cisplatin and PARP inhibitors in triple-negative breast cancer cells not harbouring BRCA1/2 mutations. 260 Adding a second PARP inhibitor, Iniparib, to treatment with gemcitabine and carboplatin improved response rates and time to progression in patients with metastatic triple-negative breast cancer in a phase II study; 261 however, a phase III follow-up study failed to confirm significant improvement. 262 Notably, recent experimental evidence has thrown doubt on the efficacy of Iniparib as a PARP inhibitor.…”
Section: Homologous Recombination Repairmentioning
confidence: 99%
“…259 Although PARP inhibitors administered as monotherapy was found ineffective in triple-negative breast cancer, experimental evidence has indicated synergistic lethality between cisplatin and PARP inhibitors in triple-negative breast cancer cells not harbouring BRCA1/2 mutations. 260 Adding a second PARP inhibitor, Iniparib, to treatment with gemcitabine and carboplatin improved response rates and time to progression in patients with metastatic triple-negative breast cancer in a phase II study; 261 however, a phase III follow-up study failed to confirm significant improvement. 262 Notably, recent experimental evidence has thrown doubt on the efficacy of Iniparib as a PARP inhibitor.…”
Section: Homologous Recombination Repairmentioning
confidence: 99%
“…Although PARP inhibitors did not statistically improve the OS, in some individual trials, they were reported to clearly increase it. For example, Novello et al 17 reported that the median OS in the PARP inhibitor arm was 12 months compared with 8.5 months in the control arm; and in another trial 20 , the OS was prolonged from 7.7 months to 12.3 months by PARP inhibitors. Research on PARP inhibitors is still ongoing, and many aspects need further improvement.…”
Section: Discussionmentioning
confidence: 99%
“…After assessing the full texts of these potentially relevant studies, 115 were excluded for the following reasons: 14 contained no relative outcomes; 88 were phase I or single-arm phase II trials; 12 were duplicate publication; and 1 used PARP inhibitors in both the experimental and control groups. Ultimately, 11 eligible RCTs [15][16][17][18][19][20][21][22][23][24][25] involving a total of 2274 patients were included for analyses. A flow diagram of the trial selection process is shown in Figure 1.…”
Section: Literature Searchmentioning
confidence: 99%
“…Furthermore, analysis of cPARP expression in breast cancer patients treated with neoadjuvant chemotherapy in the GEPARTRIO trial indicated that cPARP was a strong predictive marker for pCR in triple negative tumors, while the same time was prognostic for more aggressive tumors resulting in worst OS and DFS for patients that did not achieve pCR [65] . Despite these promising indications and the positive results from a randomized phase II trial [66] , iniparib a third generation PARP inhibitor failed to improve the outcome in the metastatic setting when added to cytotoxic chemotherapy [67] . Analogously, the interim analysis of the SOLTINeoPARP trial, a randomized phase II study that examined the efficacy of iniparib addition to weekly paclitaxel in the neoadjuvant setting of TNBC, failed to meet its primary endpoint that was pCR improvement [68] .…”
Section: Novel Agents In the Neoadjuvant Treatment Of Tnbcmentioning
confidence: 99%